(untitled) (LACCEI, 2024)
In this study, the influence of ASTM - C494 type C admixture on the compressive strength at early ages of a conventional concrete f’c 210 kg/cm2 was determined. For this purpose, temperatures were measured in concrete placed in a lightened slab using “Chema 3” admixture and specimens cured in the same work under normal conditions without admixture and with admixture, from the first hours of hydration up to 10 days, with maturity sensors. Likewise, prior to this, the calibration curve was elaborated in the laboratory using the Nurse-Saul expression with two samples the standard one, and the other one with the accelerating additive Chema 3. The research showed that the influence of the ASTM - C494 type C additive, Chema 3 additive, allowed obtaining a resistance higher than 70% at 24 hours with 181.43 kg/cm2, compared to the conventional sample which was 86.24 kg/cm2. Nevertheless, all the findings found indicated that the influence of ASTM - C494 admixture type C, Chema 3 admixture and the use of the maturity method would improve the time and costs in concrete constructions.